Bridging the Charter School Accountability Divide: Defining a Role for Nonprofit Charter School Boards. Issue 5 (June 2019) - Ford, Michael R.; Ihrke, Douglas M.
In this article, we use originally collected survey data to determine how nonprofit charter school board members in the states of Wisconsin, Michigan, and Minnesota define accountability. We find that charter board members generally define accountability downward toward student achievement and staff performance, inward toward board performance, or upward toward authorizer compliance. We use the results of the survey to make a series of public policy recommendations to help charter school boards look outward in their accountability orientation as a means of addressing the calls for increased public accountability for the charter school sector. The results add practical value to policy discussions regarding charter school accountability and theoretical value to scholars studying public and nonprofit governance reforms.